A review on fibrous materials for body armor application. (2022) - Singh Deora, Prayagraj; Khurana, Monika; Priya,; Avtar Muhal, Ram; Upadhyay, Dhruv; Goswami, Chandramani
Abstract: The emergence of novel materials every day, has developed interest worldwide in conducting more intense research in the field of materials and their development, especially in polymer-based composites that possess numerous promising properties (e.g., lighter weight, greater strength, impact resistant, and superior flexural strength) as compared to the other available materials. One of the most important applications is their utilization in the body armor for the soldiers. To protect the soldiers on the battlefield, the body armor has been utilized in personal protection system since very ancient times. To protect security personnel from a variety of ballistic risk during military conflicts and protecting soldiers or security personnel from handgun threats, the Kevlar fibres are the most common and largely used material because of high impact resistance, outstandingly high strength, stiffness to weight ratios and low weight. Kevlar aramid fibers are used widely in defence, aeronautical, bioengineering or medical and automotive industries. The investigation of ballistic application of kevlar fiber with reinforced composites and their development is an important research field. A review of kevlar composites and the ballistic impact on it, is presented in current paper. This paper concludes with the succinct evaluation of the future scopes of work in the field of reinforced-fiber composite for armour applications.